Poradniki i czasopisma jako źródło postulatywne do badań nad pożywieniem dzieci i młodzieży na ziemiach Królestwa Polskiego w latach 1795–1914 (perspektywa społeczno-kulturowa i zdrowotno-wychowawcza) - Bołdyrew, Aneta (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
Hand-books and magazines are a valuable source facilitating the research of nutrition habits, including children’s nutrition which is widely discussed by the historians from health, biological, economic, social and cultural perspectives. Doctors and hygienists in the Kingdom of Poland popularized the results of the research of West European specialists. Newspapers and hand-books described new ways of pasteurization and sterilization of milk, new means of preparing animal milk and giving it to infants. Much attention was paid to nutrition, including the appropriate diet of young people. There were many articles describing, for instance, so called, chlorosis, among girls. The need to change traditional nutrition habits was emphasised. What the young people and children ate conditioned their health and strength, which on the other hand, influenced their psycho physical condition and intellectual ability. It was therefore an important element of health education. The sources discussed are a significant basis for the research of nutrition patterns and the creation of uniform tendency and standardss concerning nutrition of children in the XIXth and at the beginning of the XXth centuries.